Anticholinergic exacerbation of psychotic symptoms : a case report - Gill, J.S.; Jambunathan, S.T.; Muhsin, M.; Abdul Rashid, R. (Faculty of Medicine, University of Malaya, 2003)
A common practice in psychiatry when treating patients is the concurrent administration of anticholinergics along with antipsychotics, either to prevent or treat extrapyramidal syndrome reactions from occurring. However, most antipsychotics have inherent anticholinergic properties themselves. Therefore, this subtype of these patients have a higher than usual risk of developing anticholinergic side-effects, of which the central nervous manifestations can mimic psychosis, and may cloud judgement on patients' progress towards their treatment.